The Influence of Level of Proficiency in the L2 and L3 on the Production of the L3 Spanish Apico-alveolar Sibilant - Sypiańska, Jolanta; Cal, Zuzanna (Research in Language, 2020)
Current Third Language Acquisition research has traditionally focused on the L2 status (e.g. Hammarberg 2001, Bardel & Falk 2007) or linguistic proximity (e.g. Cenoz 2001, Westergaard, Mitrofanova, Mykhaylyk & Rodina 2016). Limited research has been conducted on the influence of the potentially significant factor of level of proficiency, and particularly where proficiency in both the L2 (Tremblay 2006, Woll 2016) and the L3 (Hammarberg 2001, Wrembel 2010) may be considered as a conditioning factor for the shape of the L3. The aim of the current study was thus to determine the influence of L2 and L3 level of proficiency (L2LoP and L3LoP) and the interaction of the two factors on the production of the L3 Spanish apico-alveolar sibilant in a group of L1 Polish, L2 English and L3 Spanish trilinguals who had different levels of overall proficiency in the two foreign languages. The parameters of the sibilant under analysis were spectral moments: centre of gravity (M1), standard deviation (M2), skewness (M3) and kurtosis (M4) in intervocalic position in two-syllable words with initial stress. The results point to the influential role of both L2LoP and L3LoP as well as their interaction on the production of the L3 Spanish sibilant. When the level of proficiency in one of the languages was low, it allowed the other language with a higher level of proficiency to exert influence on the values of the spectral moments in the L3 sibilant. This interplay of factors furthers the understanding of how levels of proficiency in the L2 and the L3 condition the developing L3.